Resonant amplification of curvature perturbations in inflation model with periodical derivative coupling - Li-Yang Chen; Hongwei Yu; Puxun Wu (Physics Letters B, 2024)
In this paper, we introduce a weak, transient and periodical derivative coupling between the inflaton field and gravity, and find that the square of the sound speed of the curvature perturbations becomes a periodic function, which results in that the equation of the curvature perturbations can be transformed into the form of the Mathieu equation in the sub-horizon limit. Thus, the parametric resonance will amplify the curvature perturbations so as to generate a formation of abundant primordial black holes (PBHs). We show that the generated PBHs can make up most of dark matter. Associated with the generation of PBHs, the large scalar perturbations will give rise to the scalar induced gravitational waves which may be detected by future gravitational wave projects.